Implementasi Nilai-Nilai Pancasila Dalam Penyelenggaraan Pemilihan Umum Di Indonesia - Muhammad Asmawi; Lathifah Sandra Devi; Amiludin (Universitas Serang Raya, 2024)
Problem: General elections are a manifestation of the democratic system practiced by the Indonesian state, in accordance with the principles contained in the fourth principle of Pancasila. Pancasila as the state's ideological and philosophical foundation unites and inspires the nation to achieve the goal of creating a life that respects the values of divinity, humanity, unity, democracy and justice Purpose: The aim of this research is to determine the implementation of Pancasila values in holding general elections in Indonesia Methodolgy: The research was carried out using a normative descriptive analytical approach with secondary data sourced from primary, secondary and tertiary legal materials obtained from legislation, books, expert views, articles/writings and other source materials which were compiled systematically. Results/Findings: The results of the research can be concluded that applying Pancasila values in everyday life is very important, not only during elections. However, the actualization of Pancasila is also crucial in the election context to avoid violations of election principles, such as injustice, lack of integrity and lack of peace. It is hoped that the existence of Pancasila values in general elections can become a reference and goal for a democracy that is tolerant, consensual, honest and upholds unity. In this way, elections will be an effective means of political education for society, a means of people's aspirations and not just providing theories without real implementation Keywords: Pancasila Values, General Election, Democracy.